L’accompagnement des enseignants débutants du primaire : comment s’élaborent, lors des entretiens-conseils, les processus permettant la construction de savoirs professionnels ? - Alain Bécue (Recherches en Éducation)
The results we will present here are part of the researches framework based on the educational advice of beginners primary teachers, and more particularly on nature of these built knowledges and their elaborating forms. By placing us into general frame of professionnal didactic, we analyse from our recording data conclusions produced during counsel time. We propose an inventory about it, then from an example, we try to understand the articulation between demonstration, problematisation and gestion-relation dynamics processes.